PENGARUH KONSUMSI SERAT DENGAN PENGURANGAN RISIKO KANKER KOLON DI NEGARA BARAT: STUDI META ANALISIS - Masrul Masrul (Faculty of Public Health, Andalas University, 2018)
The association between dietary fibre and colorectal cancer risk is controversial. This systematic review and meta-analysis was performed to determine fibre consumption reduced risk of colorectal cancer patients in western countries.The authors conducted a meta-analysis of published research articles on fibre consumption reduced risk of colorectal cancer patients in western countries published between January 2000 and January 2018 in the online article databases of PubMed, ProQuest and EBSCO. Pooled relative risk (PRR) were calculated with fixed and random-effect models. Data were processed using Stata version 14.2 (Stata Corporation). This study reviewed 405 articles. There are 7 studies conducted a systematic review and continued with Meta-analysis. The results showed fibre consumption reduced risk of colorectal cancer patients in western countries (RR = 0.83 [95% CI 0.75-0.93]). This analysis confirmed fibre consumption reduced risk of colorectal cancer patients in western countries.